MATHEMATICAL PROBLEM-SOLVING ABILITY BASED ON COGNITIVE STYLES WITH LAPS HEURISTIC-TIME TOKEN MODEL - Silpana Fauziah; Dian Kurniawan; Eva Mulyani (Universitas Muhammadiyah Metro, 2026)
The low mathematical problem-solving ability of students, as reflected in the PISA and National Assessment results, highlights the need for effective instructional models such as the LAPS-Heuristic with Time Token Arends to develop these skills. This study aims to compare students' mathematical problem-solving abilities between the LAPS-Heuristic-Time Token and Direct Instruction models, analyze the interaction between instructional models and conceptual tempo cognitive styles, and evaluate the differences in abilities based on cognitive styles using the LAPS-Heuristic-Time Token model. Using a quantitative approach with a factorial design experiment method, data were collected from the MFFT and problem-solving ability tests, analyzed using ANOVA. The results indicate that: (1) there is no significant interaction between instructional models and cognitive styles, (2) the LAPS-Heuristic-Time Token model is more effective than Direct Instruction, and (3) there are differences in problem-solving abilities based on cognitive styles. Reflective and quick students adapt well to both models, impulsive students perform better with Direct Instruction, while slow students are better suited to the LAPS-Heuristic-Time Token model. Additional interventions are needed to support impulsive and slow students according to their characteristics.